Edukasi Pengenalan Seks Dini Pada Komunitas Anak Di Rumah Singgah Kota Bengkulu - Tita Septi Handayani; Murwati Murwati; Emi Pebriani; Jipri Suyanto (Jurnal Dehasen Untuk Negeri, 2023)
Sexual violence is still high, which is proof of low parental knowledge to apply parenting concepts and low child knowledge in general. For decreasing sexual violence, early education about sex is a solution to improving children's knowledge and a preventive measure to protect them. Community service is proposed for the children's community under KCS Odot, Bengkulu City, Indonesia. respondents to reduce the case by proposing improved children's sex education knowledge. According to the results of community service in the KCS Odot child community in Bengkulu city, children had good knowledge among 53 respondents (60%), and low knowledge among 36 respondents (40%). According to the findings, majority of participants had a good level of early sexual education.